2019
DOI: 10.3390/plants8120582
|View full text |Cite
|
Sign up to set email alerts
|

Virulent Rhodococcus fascians Produce Unique Methylated Cytokinins

Abstract: Some strains of Rhodococcus fascians exist only as epiphytes on the plant surface whereas others can become endophytic and cause various abnormalities including the release of multiple buds and reduced root growth. The abnormalities reflect the action of cytokinin. The strains that can become endophytic harbour a linear plasmid that carries cytokinin biosynthesis, activation and destruction genes. However, both epiphytic and endophytic forms can release cytokinin into culture, affect cytokinin metabolism withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The actinomycete R. fascians contains a complete CK biosynthesis pathway, including IPT, CYP450, and LOG as a part of the fas operon, which is necessary for virulence [ 22 , 46 ]. Although it has been suggested that the pathology is induced by the secretion of a mix of six synergistically acting CKs [ 22 , 95 ], more recent studies support the involvement of newly discovered CK 2-MeiP produced only by virulent R. fascians strains in the development of disease symptoms [ 4 , 96 ]. Gene encoding active CKX ( fasE ) is also present in the fas operon, but it does not have a known function in pathogenesis and appears to be superfluous [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The actinomycete R. fascians contains a complete CK biosynthesis pathway, including IPT, CYP450, and LOG as a part of the fas operon, which is necessary for virulence [ 22 , 46 ]. Although it has been suggested that the pathology is induced by the secretion of a mix of six synergistically acting CKs [ 22 , 95 ], more recent studies support the involvement of newly discovered CK 2-MeiP produced only by virulent R. fascians strains in the development of disease symptoms [ 4 , 96 ]. Gene encoding active CKX ( fasE ) is also present in the fas operon, but it does not have a known function in pathogenesis and appears to be superfluous [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the end of the 20th century, significant discoveries in plants have been made; from not even knowing if plants synthesized their own CKs (Holland, 1997), to having nearly comprehensively defined CK pathways, leading to identification of the active CKs and their corresponding conjugates (e.g., cis and trans-zeatin, iP, DZ and nucleotide, riboside, glucoside conjugates) (Kieber and Schaller, 2018). Unknown CK pathways are now rare and include those that may produce aromatic side chain CKs (Frébort et al, 2011) and the seldomly observed conjugates such as lupinic acid, a zeatin metabolite isolated from Lupinus angustifolius seedlings (Guern and Peaud-Lenoel, 2012), mono-and dimethylated isopentenyladenine CKs found in virulent Rhodococcus fascians strains (Jameson, 2019) or discadenine, iP derivative unique for slime mold Dictyostelium discoideum (Aoki et al, 2020). Another curious case is that of the hydrophobic, methylthiolated CKs (2MeS-CKs) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Rhodococcus to degrade a variety of toxic chemicals and produce bioactive substances is the most frequently reported, and more and more attention has been paid to it. Reports on the Rhodococcus also show that some of its species not only have the function of producing cytokinin but also can colonize the root system and increase the plant biomass in polychlorinated biphenyl (PCBs) contaminated soil (Jameson 2019;Vergani et al 2019).…”
Section: Discussionmentioning
confidence: 99%